Investigating the Effects of Trade Protectionism, External Capital and Financial Sector Development on Pakistan’s Balance of Payments and Current Account Reversals Impact on Growth - Zeeshan, Khan (Universiti Malaysia Sarawak, 2021)
This study employs two models to investigate Pakistan’s balance of payments behaviour in relation to some macroeconomic phenomenon. Motivation behind conducting this study is Pakistan’s lukewarm performance on its external account. Model-I with its intended objective-I, investigates the relationship between trade protectionism, financial sector development, external capital shock and balance of payments by using time series data from 1950 to 2016. Unit root and structural break properties of covariates have been tested by Augmented Dickey Fuller (ADF) and Bai–Perron tests. The Autoregressive Distributed Lag (ARDL) approach is applied to examine the cointegration between variables due to mixed orders of integration I(0)/I(1). The Autoregressive Distributed Lag results suggest long-run relationship among trade protectionism, financial sector development, external capital shock and balance of payments. Error correction model (ECM) is applied to analyze the speed of adjustment. The lagged value of the ECMt−1 is negative and significant at 5%. The value of ECMt−1 is −0.27, suggest convergence towards equilibrium in long-run with correction speed of 27% every year. Trade protectionism, financial sector development and external capital shock have significant impact on balance of payments in long run. However, in short-run only trade protectionism and external capital shock have statistically significant impacts. For Granger causality, all covariates having bi-directional causality except financial sector development. Diagnostics statistics such as, robustness and goodness of fit have confirmed stability of the Model-I. Model-I concludes applicability of Keynesian theory to balance of payments. Lastly, Model-II, to empirically address objective-II of this study, utilises Treatment Effect Regression to ascertain the economic cost associated with current account reversals first finds Sudden Stop (SS) in capital flows and declining Trade Openness (TO) carrying statistically significant probabilities in triggering current account reversals. Further, negative economic impact of these reversals is 0.74%. Model-II found structurally stable through Sbcusum estimates and concludes partial applicability of Keynesian theory to the balance of payments.